The Role of Carbon Emission Disclosure, Environmental Performance, Environmental Cost, and Sustainability Reporting on Company Value - Anggraini, Desy Ismah; Kusuma, Pramandyah Fitah (Politeknik Raflesia Press, 2024)
The aim of this research is to analyze the disclosure of carbon emissions, environmental performance, environmental costs and sustainability reports on company value in the basic materials, industrial and healthcare sectors listed on the IDX for the 2021-2022 period. This type of research is causal research with a quantitative approach. The sample in this study was 34, obtained from 17 companies in the basic materials, industrial and healthcare sectors listed on the IDX with a research period of 2 years. The results show that disclosure of carbon emissions, environmental performance, environmental costs and sustainability reports has a significant influence on company value both partially and simultaneously in companies in the basic materials, industrial and healthcare sectors listed on the IDX for the 2021-2022 period..